Group Investigation: Peningkatan Kualitas Proses Pembelajaran dan Hasil Belajar Geometri di SMP Negeri 1 Krangkeng Kabupaten Indramayu - Abdul Bashar (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to determine the quality of the learning process and learning outcomes on geometry concept material using a group investigation learning model. This research is a Classroom Action Research (PTK) which is carried out in two cycles. The subjects of the study were students of Class VIII-A SMP Negeri 1 Krangkeng Indramayu Regency The results showed that the group investigation learning model could improve the quality of the learning process as shown by an increase in interest by 13.45% (cycle I: 70.34%, cycle II: 83.76%), and an increase in student learning outcomes by 14.48% (cycle I: 68.28%, cycle II: 82.76%).